Regenerative Calcium Currents in Renal Primary Cilia - Kleene, Steven J. (Frontiers in Physiology, 2022)
Polycystic kidney disease (PKD) is a leading cause of end-stage renal disease. PKD arises from mutations in proteins, one a Ca2+-conducting channel, expressed in the primary cilia of renal epithelial cells. A common hypothesis is that Ca2+ entering through ciliary ion channels may reduce cystogenesis. The cilia have at least two Ca2+-conducting channels: polycystin-2 (PC2) and TRPV4 (transient receptor potential (TRP) cation channel, subfamily V, member 4), but how substantially they can increase intraciliary Ca2+ is unknown. By recording channel activities in isolated cilia, conditions are identified under which the channels can increase free Ca2+ within the cilium by at least 500-fold through regenerative (positive-feedback) signaling. Ca2+ that has entered through a channel can activate the channel internally, which increases the Ca2+ influx, and so on. Regenerative signaling is favored when the concentration of the Ca2+ buffer is reduced or when a slower buffer is used. Under such conditions, the Ca2+ that enters the cilium through a single PC2 channel is sufficient to almost fully activate that same channel. Regenerative signaling is not detectable with reduced external Ca2+. Reduced buffering also allows regenerative signaling through TRPV4 channels, but not through TRPM4 (TRP subfamily M, member 4) channels, which are activated by Ca2+ but do not conduct it. On a larger scale, Ca2+ that enters through TRPV4 channels can cause secondary activation of PC2 channels. I discuss the likelihood of regenerative ciliary Ca2+ signaling in vivo, a possible mechanism for its activation, and how it might relate to cystogenesis.